2022
DOI: 10.1002/ijc.33975
|View full text |Cite
|
Sign up to set email alerts
|

Modest agreement between magnetic resonance and pathological tumor regression after neoadjuvant therapy for rectal cancer in the real world

Abstract: Magnetic resonance imaging (MRI) is routinely used for preoperative tumor staging and to assess response to therapy in rectal cancer patients. The aim of our study was to evaluate the accuracy of MRI based restaging after neoadjuvant chemoradiotherapy (CRT) in predicting pathologic response. This multicenter cohort study included adult patients with histologically confirmed locally advanced rectal adenocarcinoma treated with neoadjuvant CRT followed by curative intent elective surgery between January 2014 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Posttreatment MTL has been recognized as an effective morphological predictor in assessing pCR as former studies reported ( 24 , 27 , 28 ). Another promising predictor was mrTRG, which reflected the tumor signal status after treatment and highly correlated with the tumor response ( 10 , 29 ). In the comparison of the posttreatment radiomic models (including both the pure radiomic signature and clinical-radiomics model) with the clinical model, there was still no added significant value that emerged, which was the same as the combined models.…”
Section: Discussionmentioning
confidence: 99%
“…Posttreatment MTL has been recognized as an effective morphological predictor in assessing pCR as former studies reported ( 24 , 27 , 28 ). Another promising predictor was mrTRG, which reflected the tumor signal status after treatment and highly correlated with the tumor response ( 10 , 29 ). In the comparison of the posttreatment radiomic models (including both the pure radiomic signature and clinical-radiomics model) with the clinical model, there was still no added significant value that emerged, which was the same as the combined models.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis by Jang et al found that ymrTRG scores of 1–2, which correspond to complete or good radiological regression, had a sensitivity of 70–71% and a specificity of 62–68% [ 58 , 59 ]. Moreover, the inter-reader agreement of ymrTRG is highly variable, with kappa values ranging from 0.25 to 0.8 [ 60 , 61 , 62 ].…”
Section: Rectal Mri Response Assessmentmentioning
confidence: 99%
“…41 However, there is poor association between mrTRG and pathologic TRG. [44][45][46] MrTRG has a modest sensitivity of 74% for the detection of complete response. 44 Nonetheless, this system is widely used in the United Kingdom, Canada, and some parts of the United States.…”
Section: Step 1: Review Clinical Informationmentioning
confidence: 99%
“…4). 41 However, there is poor association between mrTRG and pathologic TRG 44–46 . MrTRG has a modest sensitivity of 74% for the detection of complete response 44 .…”
Section: Step‐by‐step Approach To Restaging Rectal Mri Interpretationmentioning
confidence: 99%